향기요법이 혈액투석 환자의 수면장애, 수면 만족도, 피로에 미치는 효과 - 이은자(Lee, Eun-Ja); 김복순(Kim, Bok-Soon); 사인혜(Sa, In-Hae); 문경은(Moon, Kyung-Eun); 김정화(Kim, Jeong-Hwa) (Sŏngin Kanho Hakhoe chi, 2011)
Purpose: The purpose of this study was to identify the effects of aromatherapy on sleep disorders, satisfaction of sleep and fatigue in hemodialysis patients. Methods: The study design was a quasi-experimental study with nonequivalent control group pretest-posttest design. The subjects were assigned an experimental group (N=17) and a control group (N=17). The experimental group had inhaled lavender and sweet orange for 2 minutes three times a day for 7 days. Sleep disorders were measured using Sleep Measuring Instrument and satisfaction of sleep was gauged using Visual Analogue Scale. Fatigue was checked using Fatigue Measuring instrument. Collected data were analyzed by ${χ}^2$-test, t-test, Fisher's exact test, and paired t-test using SPSS/WIN 17.0 program. Results: There are significant differences in the sleep disorders, satisfactions of sleep and fatigue between experimental group and control group. Conclusion: Aromatherapy reduced the sleep disorders and the fatigue and increased satisfactions of sleep in hemodialysis patients. Based on the results of this study, aromatherapy can be used at the any setting as a safe and effective independent nursing intervention to sleep disorders and fatigue in hemodialysis patients.